Co-design: A central approach to the inclusion of people with disabilities (2015)
This essay seeks to position the experiences of people who live with disabilities in their interactions with the built environment that surrounds them. It argues, in part, that a hands-on approach such as co-design, which relates the personal experiences of individuals with the processes of design, can promote the inclusion of people living with disabilities. This paper also recognizes the existence and possibility of alterations to the built environment initiated by people with disabilities who, despite their disabilities, transform their surroundings to better their conditions. For these types of processes, the term user-initiated design –UID- can be defined, becoming a tool of empowerment for these individuals. These writings briefly develop the concept of user participation in design processes, analyze the use of empathic participation methods utilized in design processes with disabled individuals, and conclude that design directed towards this population cohort requires a participation that involves knowledge based on these individuals, and which should be deemed irreplaceable.